VALIDASI METODE ANALISIS KADAR ZAT AKTIF ANTIBIOTIK UNGGAS DENGAN MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI - Fejri Subriadi; Nahfia Andani (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Antibiotic is a biochemistry compound that came from an organism whereas in small dose can be used to prevent the other organism growth and also even can kill them.  For that aim, were needed an Accuration of active material composition in the antibiotic in order it can work as expectation.  To make sure of the actives material composition would be required an analysis method.  Before the method is using as a standard method, it must be done a validation so that will give an accurate and precise result.  Validation process involved some parameters which  were linearity, precision, accuration, and limit detection with each receiving conditions were determination coefficient for linearity > 0.9970,  % SD < 2%, for  precision  and recovery range was  97-103%.  The result of these research were:  determination coefficient of linearity (r2) = 0,9998, % RSD for precision of Trimethoprim  was o,4% and 0,32 % for Sulfadiazine Sodium, precision = 0,049 % RSD for Trimethoprim and 0,32 % for Sulfadiazine Sodium, accuration= 98,14 % Recovery for Trimethoprim and 98,69% for Sulfadiazine Sodium, Limit detection= 0,5020 for Trimethoprim and 0,0501 for Sulfadiazine Sodium. In sort we can say that this method can be used as routine analysis method.